Development of the physical and mathematical model of the baking process of the dough pieces in bakery ovens - Kovalyov, Alexander (Technology audit and production reserves, 2019)
The object of research is the physical and mathematical models designed to describe the heat and mass transfer inside the porous material during baking. In order to improve the quality and at the same time reduce energy consumption in production, as well as improve the technical and economic indicators of the operation of furnaces, the duration and safety of their operation, the designs of furnace units are being improved, new ones are being developed and their thermal conditions are being optimized. One of the biggest problems is the task of replacing obsolete oven designs with new ones, with automatic regulation of the thermal regime of baking, which will ensure high quality bread while reducing fuel, steam, electricity and human resources. Since the quality of products, in particular, taste, aroma, porosity, gloss, appearance and other indicators of bakery products, largely depends on the design of the furnace unit, the thermal and hygrothermal conditions of the working chamber, as well as its proper operation. These factors affect the loss during baking, which can vary from 6 to 12 %, which affects the yield of bread. This paper presents a physical and mathematical model of the process of baking dough pieces in baking ovens using the example of the industrial oven K-BOM-25 (Ukraine) developed by the author. A mathematical model of the process of baking bread in the gas channels of the baking chamber is given taking into account radiation-convective heat transfer, mass transfer taking into account the introduction of water vapor to moisten the dough pieces and turbulence of the multiphase flow. The dependence of the multiphase flow turbulence is formulated on the basis of the Euler equations averaged over Reynolds. This model allows with sufficient accuracy and detail to take into account the technological conditions and design features of modern conveyor baking ovens. And it also allows for extensive parametric studies of conjugate heat transfer in them with access to the final indicator – the quality of finished products.